Alumni Homecoming & RX Gala Dinner / Muhammad ‘Izzuddin Zamery and Aliff Zulkarnaik Zani - Zamery, Muhammad ‘Izzuddin; Zani, Aliff Zulkarnaik (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy, UiTM celebrated its 21st anniversary with a remarkable event, the Alumni Homecoming & Rx Gala Dinner 2023. Held on June 10, 2023, at Dewan Berlian, UiTM Puncak Alam, the event brought together alumni, staff, and students for an unforgettable evening of celebration and reconnection. Under the guidance of Program Director Aliff Zulkarnain Bin Zani and the advisory support of Mr Ahmad Azani Othman and Madam Massita Nordin, the event aimed to achieve several objectives. First and foremost, it sought to commemorate the faculty's 21st anniversary, recognizing the achievements and growth of the esteemed institution over the years. Additionally, the event aimed to foster strong bonds and connections among alumni, staff, and students, emphasizing the importance of a supportive and united community.